2015
DOI: 10.1037/cpb0000030
|View full text |Cite
|
Sign up to set email alerts
|

How are top companies designing and managing their high-potential programs? A follow-up talent management benchmark study.

Abstract: The assessment and development of leadership potential in organizations is a critical factor in an effective talent management strategy. Given the business environment, war for talent, and greater involvement from Boards of Directors on succession planning many organizations have prioritized their high-potential identification practices over other human capital goals. Although much has been written about theories and tools in the area of high-potential assessment, there remains little independent guidance for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(122 citation statements)
references
References 26 publications
0
112
0
3
Order By: Relevance
“…Recently, there has been an increasing trend for large corporations to dedicate efforts to the HiPo assessment and development (Church, Rotolo, Ginther, & Levine, 2015). Church et al's study (2015) found that performance is the most commonly cited contextual criteria for HiPo identification in 'top development' companies with 75 % relying on past performance and 73 % relying on current performance.…”
Section: Identification Of Hipo Employees and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been an increasing trend for large corporations to dedicate efforts to the HiPo assessment and development (Church, Rotolo, Ginther, & Levine, 2015). Church et al's study (2015) found that performance is the most commonly cited contextual criteria for HiPo identification in 'top development' companies with 75 % relying on past performance and 73 % relying on current performance.…”
Section: Identification Of Hipo Employees and Challengesmentioning
confidence: 99%
“…Employees may see HiPo status as a commitment to develop them for future roles or invest additional resource, when in fact the firm has no intention to do so (Campbell & Smith, 2010;Church et al, 2015;Silzer & Church, 2010). It may also result in reduced motivation and performance level as employees may believe that they have achieved the permanent status in the organization, and they may start looking for promotion outside the company (Dries, 2013a).…”
Section: Communication About Talent Statusmentioning
confidence: 99%
“…Research from top development companies (Church et al, 2015) has reported that over 65% have seen moderate or better performance improvement from their formal assessment programs. Although it is still too early to examine the impact of the LeAD program on participants' long-term performance, the results obtained to date have been very encouraging.…”
Section: Relationship To Performancementioning
confidence: 99%
“…In addition, it was recently featured in a white paper on leadership development (Dugan & O'Shea, 2014) published jointly by the Society for Industrial Organizational Psychology (SIOP) and the Society for Human Resource Management (SHRM). Finally, recent research with 80 large, highly respected companies recognized for their strong talent management functions (Church, Rotolo, Ginther, & Levine, 2015) suggests that the BluePrint represents a comprehensive conceptual framework encompassing what these organizations are using today internally to assess for high potentials among their leadership populations. Although there are other models of potential available to organizations in the consulting marketplace, the BluePrint is one of the few that is grounded in a comprehensive review of the academic and applied literature as well as practice in I-O psychology.…”
Section: Building a Comprehensive Model Of Leadership Potentialmentioning
confidence: 99%
“…Although the latest 360°Feedback benchmark research (3D Group, 2013) has indicated that the "desk drop" approach still is used by 7% of organizations, there has been a positive trend report over the last 10 years such that one-on-one coaching support has increased to upward of 70% of companies (3D Group, 2003(3D Group, , 2004(3D Group, , 2009(3D Group, , 2013. Further, we know from other types of benchmark research focused on senior executive and high-potential assessment efforts (e.g., Church & Rotolo, 2013;Church, Rotolo, Ginther, & Levine, 2015;Silzer & Church, 2010) that top development companies take full advantage of their 360°Feedback programs as well for both development and decision-making (e.g., identification and succession planning) purposes. Finally, as noted earlier, although not the focus of current research per se, the practice literature would suggest that 360°Feedback has become more integrated into ongoing HR, leadership development, and talent management processes and programs more broadly (e.g., Church, 2014;Church et al, 2014b;Effron & Ort, 2010;McCauley & McCall, 2014;Scott & Reynolds, 2010;Silzer & Dowell, 2010).…”
Section: Follow-up Supportmentioning
confidence: 99%